Impact of Level of Evidence on Citation of Orthopaedic Articles. Issue 23 (1st December 2021) - Scott, Bryan L.; Dirschl, Douglas R.; Landy, David C.
Abstract : Introduction: Level of evidence grading has become widely used in orthopaedics. This study reviewed clinical research articles published in leading orthopaedic journals to describe the association between level of evidence and number of future citations, which is one measure of an article's impact in the field. Methods: The first 100 clinical research articles published in 2014 by each of the Journal of Bone and Joint Surgery, Clinical Orthopaedics and Related Research, and the American Journal of Sports Medicine were reviewed for level of evidence and article characteristics. Web of Science was used to identify the number of citations of each article over the following 5 years. Univariable analyses and multivariable linear regression were used to describe the associations. Results: Three hundred articles were evaluated. Univariable analysis revealed no association between level of evidence and number of citations, with a median number of citations for level 1 articles of 23 (interquartile range [IQR], 14-49), level 2 articles 24 (IQR, 13-47), level 3 articles 22 (IQR, 13-40), and level 4 or 5 articles 20 (IQR, 10-36). Univariable analyses showed weak associations between other article characteristics and citations. Even after adjusting for other variables, the standardized regression coefficient for level 1 versus level 4 or 5 was only 0.14 and the overall model had a poor fit with an R 2 of 0.18. Conclusions: Among clinical research articles published in leading orthopaedic journals, no notable association was found between level of evidence and future citations. Clinical Relevance: Readers of the orthopaedic literature should understand that no association was found between level of evidence and future citations. Additional work is needed to better understand the effect level of evidence has on clinicians and researchers.